Reflexões junguianas sobre a cefaleia: um estudo sobre emoções, percepções e fantasias - Bissolli, Giancarlo Dedone (2021)
Migraine is an umbrella term that encompasses different types of headaches. Much research has shown a connection between migraine and a range of emotional changes and psychiatric disorders. This study aimed to understand, from a symbolic point of view, migraine in adults, investigating possible ideas, fantasies, emotions, feelings and perceptions regarding this condition, as well as its possible associations with depression and anxiety. This was an exploratory mixed method research, with a quantitative stage, in which 133 adults (88.7% female and 11.3% male) responded an online questionnaire, and subsequently, a qualitative stage, with interviews with eight randomly selected participants. The results showed that most participants had mild to moderate levels of depression and anxiety, reported that their headaches were triggered by emotional issues, notably anxiety (75.2%) and anger (48.9%), and by situations of stress relating to interpersonal problems and losses. It was found that the levels of anxiety and depression were positively correlated with the impact on performing daily tasks, and negatively correlated with the belief in the effectiveness of coping strategies and the feeling of confidence to cope with headaches. The interviews and symbolic content analyzed revealed an excessively controlling and organized attitude of the participants and, behind it, the migraine appears as a disruptive element that promotes disorganization and confronts its control. The understanding of results was based on reflections from Analytical Psychology and Jungian Psychosomatics. Migraine was considered a psychosomatic condition that presents itself as the transduction from a psychic conflict to the body and acts with three main functions: defensive, compensatory and transformative. Migraine is understood as a complex disease in which both emotional and symbolic factors play a role in its formation and maintenance, and it can be seen as a problem that can be addressed in the analytical process